Core concept identification in STEM and related domain education: a scoping review of rationales, methods, and outputs - Alison U. Etukakpan; Megan G. Waldhuber; Kristin K. Janke; Adeladlew Kassie Netere; Thomas Angelo; Paul J. White (Frontiers in Education)
Core concepts—fundamental, enduring, and discipline-specific ideas—are essential for enhancing comprehension and facilitating knowledge acquisition for STEM and health-related learners. Since the 1990s, many articles have been published in STEM and health-related domains explaining the need and/or the value of identifying and utilizing core concepts in education. However, little research has explored the reasons for and methods for identifying the core concepts that may be useful to curriculum designers, course coordinators, instructors and assessment specialists in STEM and health sciences faculties. This scoping review examines the research on core concept identification within the context of STEM and Health-related domains of education with three objectives: (1) to describe the rationale for identifying core concepts; (2) to identify the study designs and research approaches employed; and (3) to present key outputs about core concept identification across domains. Using scoping review methodology aligned with Arksey and O’Malley’s framework, eligible studies addressing core concept identification with a methodological description of how these concepts were identified for formal education in a STEM or health-related domain were identified through Medline ALL and Scopus database, complemented with backward citation of all included full-text references. Thirty research publications were identified, and data was systematically extracted and analyzed according to the review objectives. The review identified seven rationales for core concept identification, the most common being content prioritization, which addresses the need to identify essential teaching content within expanding knowledge bases. Mixed methods were the predominant research approach (n = 20), with various data collection and analysis methods, most of which are aligned with pragmatic philosophical worldviews, strongly emphasizing expert-driven techniques. These findings provide valuable insights for educators and researchers engaging in core concept identification, offering guidance for methodology selection and implementation while highlighting areas requiring further development in the field.